1991
DOI: 10.1152/jappl.1991.71.6.2352
|View full text |Cite
|
Sign up to set email alerts
|

Responses of baboons to prolonged hyperoxia: physiology and qualitative pathology

Abstract: Cardiopulmonary responses to prolonged hyperoxia and their relationships to the development of lung pathology have not been fully characterized in primates. In this study, circulatory hemodynamics and pulmonary function, vascular permeability, and leukocyte sequestration were measured in male baboons after 100% O2 exposure and related to ultrastructural changes of lung injury by electron microscopy. Three groups of animals were exposed to 100% O2 in an exposure cage for 40, 66, and 80 h, respectively. A fourth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 0 publications
1
60
0
1
Order By: Relevance
“…High concentrations of oxygen may perpetuate lung injury and result in persistent inflammation indistinguishable from that seen in ARDS (28 -30). Hyperoxia-induced lung injury is characterized by noncardiogenic pulmonary edema, alveolar hyaline membrane formation, type I alveolar epithelial cell injury, type II alveolar epithelial cell hyperplasia, neutrophil infiltration, alveolar hemorrhage, and increased alveolar wall thickness (31,32). As the lung injury progresses, the interstitium becomes infiltrated with leukocytes, FIGURE 7.…”
Section: Discussionmentioning
confidence: 99%
“…High concentrations of oxygen may perpetuate lung injury and result in persistent inflammation indistinguishable from that seen in ARDS (28 -30). Hyperoxia-induced lung injury is characterized by noncardiogenic pulmonary edema, alveolar hyaline membrane formation, type I alveolar epithelial cell injury, type II alveolar epithelial cell hyperplasia, neutrophil infiltration, alveolar hemorrhage, and increased alveolar wall thickness (31,32). As the lung injury progresses, the interstitium becomes infiltrated with leukocytes, FIGURE 7.…”
Section: Discussionmentioning
confidence: 99%
“…This injury is thought to be initiated by the local generation of reactive oxygen species (ROS), and as it evolves, pulmonary structural damage becomes extensive, accompanied by airway inflammation, alveolar and interstitial edema, and reduced lung function (Kapanci and Weibel, 1969;Crapo, 1986). The components of the inflammatory response include increased levels of pro-inflammatory cytokines, such as tumor necrosis factor-alpha (TNF-α), interleukin (IL)-1beta and IL-6 (Johnston et al 1997), and the recruitment of neutrophils to the distal airspaces (Johnston et al 1997;Keeney et al 1995;Fracica et al 1991;Bureau et al 1985). The roles of neutrophils in hyperoxic lung injury remain unclear, but it has been suggested that the neutrophils in the airways release oxidants that contribute to tissue damage (Keeney et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperoxia paradoxically raises lavageable VEGF levels. This latter effect and that on VEGF mRNA level but not protein is abrogated by recovery in reduced There are many pathologic manifestations of hyperoxic lung injury, but widespread endothelial cell damage and necrosis, with resultant high pulmonary microvascular permeability, are of particular importance (1,2). The normal resolution of this vascular damage requires angiogenesis (3).…”
mentioning
confidence: 99%